An experimental and numerical study of fluidized bed drying of hazelnuts - GÜL, MEHMET ZAFER (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
The fluidized bed drying of hazelnuts was performed and a laboratory scaled fluidized bed was constructed to obtain experimental data. A mathematical model for the simulation of simultaneous unsteady heat and mass transfer in fluidized bed drying of large particles was performed. Solution of the equation set was carried out by using Crank-Nicholson implicit method within finite volume frame work. A good agreement between the numerical and the experimental results was observed. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: fluidized bed; drying; hazelnuts; mathematical model; validation; PARTICLES